(untitled) (PLA Inside Out: An International Journal on Theory, Research and Practice in Prior Learning Assessment, 2025)
CEDEFOP has created this vast “information hub” that collects a significant amount of information regarding knowledge/skills that extend beyond formal learning and include learning that occurs in non-formal and informal settings (including on the job, at home, and in the community). This tool links the 2023 European Guidelines for Validating Non-formal and Informal Learning and The European Inventory of Non-formal and Informal Learning, and is particularly useful for individuals, institutions, and nations that are developing policies, practices, and resources relevant to validation. Our sincere thanks to Ernesto Villalba-Garcia who has made this resource available to us. https://www.cedefop.europa.eu/en/tools/validation-non-formal-informal-learning